The changing public role in a rice economy approaching self-sufficiency: the case of Bangladesh - Goletti, Francesco (International Food Policy Research Institute, 1994)
Bangladesh, which has been a country of chronic food deficits, now appears to be nearing self-sufficiency in rice. Production of rice, the major food staple of the country, grew at a rate of 2.7 percent in the 1980s, while population grew at a rate of 2.0 percent. The gap between production and the foodgrain requirements of the population is clearly narrowing, although the need to import wheat will continue for the rest of this decade. The sustained and increasingly stable growth of rice production during the 1970s and 1980s is closely related to the introduction of high-yielding varieties, mainly the winter boro rice crop, which rose from 21 percent of total rice production in 1972/73 to 35 percent in 1989/90. The two main rice crops, aman and boro, tend to have contrary patterns of production increase and decrease within a given year. Now that boro rice has a larger share in total production, this intrayear compensation affords a more regular flow of production and a changed pattern of seasonality characterized by smoother price fluctuations.